Transformation from a Partnership to an Incorporated Company: A Case of Kleenson Marketing (Journal of Business Management and Accounting, 2018)
Many small businesses start with sole proprietorship or partnership. When the business grows or the entrepreneurs intend to expand their businesses to a larger area or export to overseas markets, the current setup might not be suitable anymore. The entrepreneurs might need to transform into another form of business organization, a small and medium enterprise (SME) with an incorporated company status might be more suitable, have better corporate perceptions, ability to raise fund for business expansion, tax planning opportunity, business continuity. This article is aimed at looking at the transformation process that took place in a company from partnership based to an incorporated company. Transformation of businesses for small business owners might not be a big challenge for them, since they know how to run their business and the use of the latest marketing trend. However, transformation in terms of forms of business organizations and corporate compliance requirements would be a challenge for those who are not aware of the requirements. This article provides an understanding of common forms of business organizations in Malaysia, outline the factors to consider, reasons and benefits to convert business from a partnership to an incorporated company, and ensure compliance requirements after incorporation. This article serves as a guideline for a partnership company which is expanding to transform into an incorporated company form of business organization in Malaysia.